2021
DOI: 10.1111/nph.17616
|View full text |Cite
|
Sign up to set email alerts
|

A natural single‐nucleotide polymorphism variant in sulfite reductase influences sulfur assimilation in maize

Abstract: Summary Plants absorb sulfur from the environment and assimilate it into suitable forms for the biosynthesis of a broad range of molecules. Although the biochemical pathway of sulfur assimilation is known, how genetic differences contribute to natural variation in sulfur assimilation remains poorly understood. Here, using a genome‐wide association study, we uncovered a single‐nucleotide polymorphism (SNP) variant in the sulfite reductase (SiR) gene that was significantly associated with SiR protein abundance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 67 publications
(104 reference statements)
0
4
0
Order By: Relevance
“…In addition, free energy prediction of mRNA secondary structure revealed that the Hap2 ZmIRX15A mRNA was more stable than the Hap1 ZmIRX15A mRNA (Figure 3a). It has been well known that less RNA secondary structure of minimum free energy (MFE) correlates with higher mRNA stability and translation efficiency (Akdeli et al ., 2014; Jiang et al ., 2021; Mauger et al ., 2019; Wang et al ., 2006). As a result, ZmIRX15A Hap2 mRNA tended to have a higher probability of forming a relatively more stable secondary structure, presumably affecting the translation of ZmIRX15A mRNA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, free energy prediction of mRNA secondary structure revealed that the Hap2 ZmIRX15A mRNA was more stable than the Hap1 ZmIRX15A mRNA (Figure 3a). It has been well known that less RNA secondary structure of minimum free energy (MFE) correlates with higher mRNA stability and translation efficiency (Akdeli et al ., 2014; Jiang et al ., 2021; Mauger et al ., 2019; Wang et al ., 2006). As a result, ZmIRX15A Hap2 mRNA tended to have a higher probability of forming a relatively more stable secondary structure, presumably affecting the translation of ZmIRX15A mRNA.…”
Section: Resultsmentioning
confidence: 99%
“…To assess any changes in mRNA structure caused by the variant InDel1089, qRT‐PCR experiments were performed using primers DMS‐F1 (nucleotides 188–205 of the ZmIRX15A exon2), DMS‐F2 (nucleotides 68–88 of the ZmIRX15A 3′UTR), and DMS‐R (complementary to nucleotides 106–125 of the ZmIRX15A ‐UTR). The truncation rate for InDel1089 mRNA was calculated as follows (Jiang et al ., 2021): 12()Cq()DMSgoodbreak−normalF2/normalRgoodbreak−Cq()DMSgoodbreak−normalF1/normalRDMStreated2()Cq()DMSgoodbreak−normalF2/normalRgoodbreak−Cq()DMSgoodbreak−normalF1/normalRuntreated (Cq (DMS‐F2/R), PCR cycle number using DMS‐F2/DMS‐R primer; Cq (DMS‐F1/R), PCR cycle number using DMS‐F1/DMS‐R primer).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Combining GWAS and gene-based association analysis to identify causal gene of maize tolerance to Pb stress GWAS is an effective method to dissect the genetic basis of quantitative traits. It has been widely applied to identify a variety of complex traits in plant species, including Pb accumulation (Zhao et al, 2018), protein abundance (Jiang et al, 2021), root configuration-related traits (Wang et al, 2019), yield-related traits (Sharma et al, 2018), salt tolerance (Ma et al, 2021b), and so on. Gene-based association analysis is the most widespread method for associating the functional variation loci of candidate genes with the phenotypes they produce (Li et al, 2019).…”
Section: Heterologous Expression Of Zmbzip107 Decreasing Pb Uptake In...mentioning
confidence: 99%